THE INTEGRITY OF ISLAMIC BUSINESS ETHICS AMID URBAN ECONOMIC DYNAMICS: AN ANALYSIS OF M. UMER CHAPRA’S PERSPECTIVE ON MUSLIM MERCHANTS IN MARTAPURA - Sauqi, Muhammad; Mustofa, Imam; Azhar, Alias; Fahmi Al Amruzi, M.; Jalaluddin, Jalaluddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2026)
This research aims to analyze the business practices of Muslim traders in Martapura City through the framework of Islamic business ethics of Muhammad Umer Chapra, which includes justice (al-'Adl), moral motivation, spiritual accountability, and social welfare. Although Martapura is known sociologically as the “City of Santri”, the tension between traditional religiosity values and the demands of a competitive urban economy often creates ambiguities in the implementation of business ethics in the field that remain underexplored empirically. This qualitative research employed a phenomenological approach. The data was collected through in-depth interviews with eight purposively selected informants, consisting of five traders and three customers in the Martapura trading area. The results of the study show that traders have internalized the principle of fairness through transparency of scales and equal treatment to consumers. Moral motivation and spiritual accountability were reflected in the traders’ eschatological awareness, particularly their belief in the afterlife, that prevents fraudulent practices. In addition, the aspect of social welfare was manifested through the mechanism of zakat and alms that are institutionalized in the local trade culture. These findings confirm that the integrity of Islamic business ethics in Martapura is not merely expressed through individual behavior, but is also shaped by social cohesion and local religious identity, both of which function to mitigate the negative impacts of urban economic competition.